2020
DOI: 10.1021/acscentsci.0c01488
|View full text |Cite
|
Sign up to set email alerts
|

Large Single Crystals of Two-Dimensional π-Conjugated Metal–Organic Frameworks via Biphasic Solution-Solid Growth

Abstract: Two-dimensional (2D) π-conjugated metal–organic frameworks (πMOFs) are a new class of designer electronic materials that are porous and tunable through the constituent organic molecules and choice of metal ions. Unlike typical MOFs, 2D πMOFs exhibit high conductivity mediated by delocalized π-electrons and have promising applications in a range of electrical devices as well as exotic physical properties. Here, we develop a growth method that generates single-crystal plates with lateral dimensions exceeding 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…Altogether, structural, electrochemical, spectroscopic, and magnetic data support the increase of HOTP oxidation state and progressive quinoidal character from 1 to 3 . The electron density on HOTP delocalizes significantly for all HOTP charge states, and is in line with the observed excellent charge delocalization in MOFs made with the same ligand [15, 34] . Indeed, the comproportionation constant describing HOTP‐based redox events is among the largest for complexes with triphenylene bridges [14, 19, 22, 23, 27] .…”
Section: Discussionsupporting
confidence: 80%
“…Altogether, structural, electrochemical, spectroscopic, and magnetic data support the increase of HOTP oxidation state and progressive quinoidal character from 1 to 3 . The electron density on HOTP delocalizes significantly for all HOTP charge states, and is in line with the observed excellent charge delocalization in MOFs made with the same ligand [15, 34] . Indeed, the comproportionation constant describing HOTP‐based redox events is among the largest for complexes with triphenylene bridges [14, 19, 22, 23, 27] .…”
Section: Discussionsupporting
confidence: 80%
“…Altogether,s tructural, electrochemical, spectroscopic, and magnetic data support the increase of HOTP oxidation state and progressive quinoidal character from 1 to 3.T he electron density on HOTP delocalizes significantly for all HOTPcharge states,and is in line with the observed excellent charge delocalization in MOFs made with the same ligand. [15,34] Indeed, the comproportionation constant describing HOTP-based redox events is among the largest for complexes with triphenylene bridges. [14,19,22,23,27] In the three trinuclear nickel complexes reported here,t he HOTP moieties take spin configurations of singlet diradical, monoradical, and closed-shell as they become doubly,t riply,o r quadruply oxidized relative to the fully reduced HOTP 6À .…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] One previous study undertaking this strategy for aC u-based MOF demonstrated feasibility,b ut ultimately provided little insight because only as ingle ligand oxidation state could be isolated and characterized. [14] Here,w ei solate model complexes related to the conductive MOF nickel hexaoxytriphenylene (Ni 9 HOTP 4 ) [1,15] in three consecutive oxidation states: [(Me 3 TPANi) 3 (HOTP)](BF 4 ) n (Me 3 TPA = N,N,N-tris[(6methyl-2-pyridyl)methyl]amine) (n = 2, 3, 4f or complexes 1, 2, 3), with charge states of À4, À3, and À2, respectively,on the HOTP fragment (Scheme 1b). HOTP serves as ap articularly attractive target because its three catechol units are,in principle,e ach capable of engaging in two consecutive oneelectron reversible redox couples in the catecholate-semiquinonate-quinonate (cat-sq-q) sequence (Scheme 1a), affording up to six different oxidation states for aN i 3 HOTP complex.…”
Section: Introductionmentioning
confidence: 99%
“…We anticipate that the fundamental study presented herein will open the avenue for in‐depth investigation of other conductive frameworks and 2D layered materials through the exploitation and manipulation of different types of stacking forces. Future studies using devices fabricated from large single crystals and precisely controlled number of layers of the 2D layered MOFs should clarify the anisotropic and intrinsic electronic properties and minimize the nontrivial effects of structural defects, impurities, and grain boundaries in this general class of materials [1b, 11b,d] …”
Section: Discussionmentioning
confidence: 99%